2011
DOI: 10.1097/aog.0b013e3182118790
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal pH-Balanced Gel for the Control of Atrophic Vaginitis Among Breast Cancer Survivors

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 20 publications
0
73
0
2
Order By: Relevance
“…Vaginal pH-balanced gel improved both vaginal dryness and dyspareunia, lowered vaginal pH and enhanced vaginal maturation index with minimal side effects (mild irritation during the first four weeks of therapy administration) [Lee et al 2011]. These findings suggest that vaginal pH-balanced gel is an alternative option to alleviate vulvovaginal symptoms in symptomatic patients and can ultimately protect against vaginal colonization by nonvaginal microflora, which predispose women to vaginal infections and UTIs.…”
Section: Nonhormonal Treatment Optionsmentioning
confidence: 73%
See 1 more Smart Citation
“…Vaginal pH-balanced gel improved both vaginal dryness and dyspareunia, lowered vaginal pH and enhanced vaginal maturation index with minimal side effects (mild irritation during the first four weeks of therapy administration) [Lee et al 2011]. These findings suggest that vaginal pH-balanced gel is an alternative option to alleviate vulvovaginal symptoms in symptomatic patients and can ultimately protect against vaginal colonization by nonvaginal microflora, which predispose women to vaginal infections and UTIs.…”
Section: Nonhormonal Treatment Optionsmentioning
confidence: 73%
“…A randomized, double-blinded, placebo-controlled study investigated the effect of a vaginal pH-balanced gel (containing lactic acid) on vaginal symptoms and atrophy in breast cancer survivors [Lee et al 2011]. Vaginal pH-balanced gel improved both vaginal dryness and dyspareunia, lowered vaginal pH and enhanced vaginal maturation index with minimal side effects (mild irritation during the first four weeks of therapy administration) [Lee et al 2011].…”
Section: Nonhormonal Treatment Optionsmentioning
confidence: 99%
“…One small study of 45 patients with breast cancer who experienced vaginal dryness and dyspareunia found that Replens and a placebo preparation were equally effective in relieving symptoms [72]. In a separate randomized, placebocontrolled study that included 86 women, the vaginal pHbalanced gel was more effective in relieving both dryness and dyspareunia [73]. The frequency of use of these vaginal moisturizes is guided by the severity of symptoms, and use can be once every 3 days to daily.…”
Section: Nonendocrine Therapiesmentioning
confidence: 99%
“…Of four studies selected for inclusion criteria [17][18][19][20], one was presented in abstract form [18] and one was a letter [17], and thus limited study information was available. Characteristics of the studies regarding study design and interventions compared, sample size, patient eligibility criteria and patient demographics are described in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%